2021
DOI: 10.1002/hbm.25633
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in representational similarity of first and second languages in the bilingual brain

Abstract: Current theories of bilingualism disagree on the extent to which separate brain regions are used to maintain or process one's first and second language. The present study took a novel multivariate approach to address this question. We examined whether bilinguals maintain distinct neural representations of two languages; specifically, we tested whether brain areas that are involved in processing word meaning in either language are reliably representing each language differently, and whether language representat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Overall, the reviewed evidence highlights that the core cortical network activated by words in different languages is the same, with relatively minor differences that could be explained by differences in proficiency in the two languages, the use of those languages, or the relative age of acquisition. Nonetheless, when considering balanced bilinguals, highly proficient in both languages, no differences are typically observed across neuroimaging techniques: left hemisphere frontotemporal regions are activated across languages and tasks (Hernandez et al, 2000; Jones et al, 2012), as well as, to a lesser extent, homologous regions of the right hemisphere (e.g., Geng et al, 2022; Nichols et al, 2021), especially in lexical/semantic tasks (Sulpizio et al, 2020). This “null effect” supports the idea that the neural infrastructure supporting the two languages is not differentiated and, consequently, that the lexical repertoire of the bilingual mind is integrated and indistinct for the two languages.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the reviewed evidence highlights that the core cortical network activated by words in different languages is the same, with relatively minor differences that could be explained by differences in proficiency in the two languages, the use of those languages, or the relative age of acquisition. Nonetheless, when considering balanced bilinguals, highly proficient in both languages, no differences are typically observed across neuroimaging techniques: left hemisphere frontotemporal regions are activated across languages and tasks (Hernandez et al, 2000; Jones et al, 2012), as well as, to a lesser extent, homologous regions of the right hemisphere (e.g., Geng et al, 2022; Nichols et al, 2021), especially in lexical/semantic tasks (Sulpizio et al, 2020). This “null effect” supports the idea that the neural infrastructure supporting the two languages is not differentiated and, consequently, that the lexical repertoire of the bilingual mind is integrated and indistinct for the two languages.…”
Section: Introductionmentioning
confidence: 99%
“…How the native and second languages are represented in the brain has been a topic of interest to researchers for some time (Illes et al, 1999 ; Li et al, 2019 ; Ou et al, 2020 ; Qu et al, 2019 ; Xu et al, 2017 ). By comparing neural activity elicited by different languages in bilinguals or multilinguals, existing research has revealed that native and second languages have common activations in a wide neural network, including the prefrontal cortex, temporoparietal regions, and occipitotemporal regions (Cao et al, 2013 ; Chee et al, 1999 ; Dong et al, 2020 ; Feng et al, 2020 ; Klein et al, 1995 ; Li et al, 2019 ; Nichols et al, 2021 ; Ou et al, 2020 ; Wang et al, 2011 ; Wong et al, 2016 ; Xue et al, 2004 ; Yokoyama et al, 2006 ). Subsequent studies further revealed that linguistic factors (e.g., language distance between native and second languages) and learner‐related factors (e.g., proficiency and age of acquisition in the second language) modulated the degree of similarity in activation patterns between native and second languages (Berken et al, 2015 ; Bloch et al, 2009 ; Cargnelutti et al, 2019 ; Li et al, 2021 ; Liu & Cao, 2016 ; Nichols et al, 2021 ; Xu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…By comparing neural activity elicited by different languages in bilinguals or multilinguals, existing research has revealed that native and second languages have common activations in a wide neural network, including the prefrontal cortex, temporoparietal regions, and occipitotemporal regions (Cao et al, 2013 ; Chee et al, 1999 ; Dong et al, 2020 ; Feng et al, 2020 ; Klein et al, 1995 ; Li et al, 2019 ; Nichols et al, 2021 ; Ou et al, 2020 ; Wang et al, 2011 ; Wong et al, 2016 ; Xue et al, 2004 ; Yokoyama et al, 2006 ). Subsequent studies further revealed that linguistic factors (e.g., language distance between native and second languages) and learner‐related factors (e.g., proficiency and age of acquisition in the second language) modulated the degree of similarity in activation patterns between native and second languages (Berken et al, 2015 ; Bloch et al, 2009 ; Cargnelutti et al, 2019 ; Li et al, 2021 ; Liu & Cao, 2016 ; Nichols et al, 2021 ; Xu et al, 2021 ). For example, compared to late bilinguals or bilinguals with lower second language proficiency, early bilinguals or bilinguals with higher proficiency in the second language showed less activation differences between the two languages (Chee et al, 2001 ; Gao et al, 2017 ; Lee et al, 2003 ; Sebastian et al, 2011 ; Wartenburger et al, 2003 ; Xu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is crucial to observe the effect of learning Chinese as a second language on the neural substrates of semantic processing, particularly the ventral pathway ( Wang et al, 2019 ). The ventral pathway has been associated with semantic processing, including the middle occipital gyrus, fusiform gyrus, middle/superior temporal gyrus, and IFG ( Fan et al, 2020 ; Nichols et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%